Optimising the Hygiene Quality of Salted Fish to Improve the Economy of Coastal Communities - Sadat, Anwar; Sa'ban, LM Azhar; Nastia, Nastia; Lawelai, Herman; Yusna, Yusna (Edumedia Solution, 2025)
Optimising the hygienic quality of salted fish is critical for coastal communities seeking to grow their economies and overcome the problems of Gaya Baru Village's Fishermen's Home Industry (IRT). Partners face difficulties drying fish when it rains, storing salted fish is still very simple, and partners lack good marketing techniques. The goal of this Community Service (PkM) is to: 1) increase technological knowledge; 2) increase the entrepreneurial spirit and motivation of partner entrepreneurs; and 3) improve HR capabilities in business management, production, and finance. The PkM has resulted in the development of two salted fish businesses in Gaya Baru village, allowing those who work to become self-sufficient.